Validation of the Citizenship Education Model in Enhancing Civic Culture in the Cultural and Artistic Organization of Tehran Municipality - Haji Mollarabi, Ali; Rashidi, Zolfaghar; Sepehrnia, Rozita (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective:  The objective of this study was to validate a citizenship education model for enhancing civic culture within the Cultural and Artistic Organization of Tehran Municipality.Methods and Materials: This study employed an applied, quantitative approach using a descriptive–survey design. The statistical population consisted of 1,857 employees and experts of the Cultural and Artistic Organization of Tehran Municipality, from which a sample of 384 participants was selected through simple random sampling based on Cochran’s formula at a 95% confidence level. Data were collected using a researcher-developed questionnaire derived from the qualitative phase and grounded theory components, designed on a five-point Likert scale. Content validity was confirmed by expert review, and reliability was established using Cronbach’s alpha (α > 0.70). Data analysis was conducted using descriptive and inferential statistics, and structural equation modeling (SEM) based on the Partial Least Squares (PLS) approach was applied to test the conceptual model and examine relationships among variables.Findings: The results indicated that causal factors, including heterogeneous socio-cultural context (β = -0.337), cultural diversity (β = -0.255), neglect of citizenship rights (β = -0.377), erosion of social capital (β = -0.293), and inefficiency of educational programs (β = -0.274), had significant negative effects on civic culture. Contextual conditions such as access to demographic data (β = 0.351) and the background of citizenship education programs (β = 0.509) positively influenced the implementation of strategies. Intervening factors (β = 0.281) significantly affected the effectiveness of strategies. Furthermore, strategies including localized content design (β = 0.379), interactive and multimedia methods (β = 0.285), local instructor networks (β = 0.314), peer support groups (β = 0.346), participatory events (β = 0.382), and monitoring and evaluation (β = 0.385) demonstrated significant positive effects on outcomes, including civic culture, social capital, civic participation, and urban quality of life.Conclusion: The validated model demonstrates that effective citizenship education, supported by appropriate contextual conditions and strategic interventions, can significantly enhance civic culture, strengthen social capital, and improve civic participation and urban quality of life, providing a robust framework for policy and practice in urban cultural organizations.